1998
DOI: 10.1093/hmg/7.3.471
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant congenital cataract associated with a missense mutation in the human alpha crystallin gene CRYAA

Abstract: Congenital cataracts are a common major abnormality of the eye that frequently cause blindness in infants. At least a third of all cases are familial; autosomal dominant congenital cataract (ADCC) appears to be the most common familial form in the Western world. We have mapped an ADCC gene in family ADCC-2 to chromosome 21q22.3 near the alpha-crystallin gene CRYAA. By sequencing the coding regions of CRYAA, we found that a missense mutation, R116C, is associated with ADCC in this family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
229
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(238 citation statements)
references
References 28 publications
8
229
0
Order By: Relevance
“…77,78 Consistent with these observations, the chaperone-like ability of R116C and R120G was found substantially decreased. 79,80 The results reported here and also from earlier studies [73][74] reveal that the two mutants apparently display much weaker antiapoptotic ability.…”
Section: Antiapoptotic Mechanisms Of A-crystallinssupporting
confidence: 79%
“…77,78 Consistent with these observations, the chaperone-like ability of R116C and R120G was found substantially decreased. 79,80 The results reported here and also from earlier studies [73][74] reveal that the two mutants apparently display much weaker antiapoptotic ability.…”
Section: Antiapoptotic Mechanisms Of A-crystallinssupporting
confidence: 79%
“…Although mature miRNAs are only approximately 22 nt in length, they are much more abundant than mRNAs (Lim et al, 2003b), which suggested to us that an oligonucleotide probe with a single hapten could bind to a sufficient number of copies of a specific miRNA to compensate for the reduced number of haptens per probe. Highly stringent wash conditions have been developed for the detection of mismatches in DNA after hybridization with labeled DNA oligonucleotide probes, based on the use of tetramethyl ammonium chloride (TMAC) to make the melting temperature (Tm) of the oligonucleotide and its target a function of duplex length, independent of GC content (Wood et al, 1985;Jacobs et al, 1988;Litt et al, 1998). TMAC also reduces the melting temperature of an RNA:RNA duplex to that of an equivalent DNA: DNA duplex (Golas et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescein-labeled DNA oligonucleotide probes also detected endogenous miRNAs, but with substantially higher background on tissue sections, possibly from nonspecifically bound probe (unpublished observations). To provide sequence specificity, we have used TMAC-based washes similar to those used for allele-specific oligonucleotide probes (Litt et al, 1998). For the abundant miRNA miR-124a, we found that two single nucleotide mismatches with the probe essentially abolished the hybridization signal.…”
Section: Discussionmentioning
confidence: 99%
“…66,71 For example, a missense mutation in the human alpha-A-crystallin gene CRYAA was reported to accompany autosomal dominant congenital cataracts (ADCC) in one family. 63 In another study, it was found that progressive juvenileonset punctate cataracts were caused by a mutation in the gamma-D-crystallin gene. 72 The investigation focused on three generations of a family with hereditary progressive cataracts, transmitted as a fully penetrant dominant trait.…”
Section: Cataractsmentioning
confidence: 99%
“…The association of cataracts with mutations in the crystallin genes, leading to protein misfolding, has been reported on several occasions. 61,[63][64][65][66] The implicated, mutated crystallin genes include CRYAA (alpha-A-crystallin), 63 CRYAB (alpha-B-crystallin), 67,68 CRYBB2 (beta-B-crystallin), 69,70 and CRYGC (gamma-C-crystallin). 66,71 For example, a missense mutation in the human alpha-A-crystallin gene CRYAA was reported to accompany autosomal dominant congenital cataracts (ADCC) in one family.…”
Section: Cataractsmentioning
confidence: 99%